National Regulatory Authorities in Regulation (EU) No 1227/2011 of the European Parliament and of the Council of 25 October 2011 on Wholesale Energy Market Integrity and Transparency - Przemyslaw ZDYB (Communications of International Proceedings, 2021)
The aim of this paper is to characterize selected legal instruments stipulated in Regulation (EU) No 1227/2011 of the European Parliament and of the Council of 25 October 2011 on wholesale energy market integrity and transparency. The REMIT regulation identifies two basic prohibitions: prohibition of insider trading; prohibition of manipulating or attempting to manipulate on wholesale energy markets. In turn, every market participant is obliged to publicly disclose inside information. Given the above, the paper proposes that rights assigned to NRAs be systematized according to the criterion of occurrence in REMIT of competence norms that authorize and oblige these authorities to take specific actions. The most important of them include inspection-related powers, maintaining registers of market participants and imposing administrative sanctions for non-observance of orders and prohibitions specified in the Regulation. The reflections carried out by means of an analysis of applicable laws allow the author to formulate a positive assessment of granting national regulatory authorities a significant role in the application of REMIT, thanks to which they have a crucial influence on the achievement of the desired state of a single energy market in the European Union.
Keywords: National Regulatory Authorities; Wholesale Energy Markets; REMIT